Organización contable al “almacén mediconf” del señor Manuel Alejandro Ordóñez naranjo de la ciudad de Loja, periodo del 01 de abril al 30 de junio del 2022. - Ordóñez Riofrio, Cristina Belén (2023)
The following research titled ACCOUNTING ORGANIZATION OF THE "MEDICONF WAREHOUSE" OF MANUEL ALEJANDRO ORDÓÑEZ NARANJO FROM THE CITY OF LOJA, THROUGH APRIL 1 TO JUNE 30, 2022, was developed as a means of complying with the academic regime regulations prior to obtaining the degree of Engineer in Accounting and Auditing; as well as in order to meet the objectives stated in the project regarding the warehouse's accounting organization. A thorough analysis of the company's nature, scope, and line of business was carried out, as well as information collected from the owner, in order to meet the proposed objectives. Additionally, a chart of accounts customized to the warehouse's needs was developed. Subsequently, it was necessary to order and code numerically all accounts of assets, liabilities, equity, expenses, costs, and income, describing both their conceptual part and their respective movements.; subsequently, based on the plan described above, a physical verification of all the goods, securities and obligations held by the "Mediconf" Warehouse was carried out, which resulted in total assets of $ 37. 393.11, total liabilities of $ 12,500.00, and its equity of $ 24,893.11. As a final step, the source of documentation was compiled and organized, along with other information supporting the company's economic-financial operations, and recorded it in the previously prepared auxiliary books, whose summary was then recorded in the journal, along with other current operations, leading to the presentation of the financial statements., where the statement of financial position reflects total assets of $ 38. 113, 98, total liabilities of $ 12.805,81 and consequently equity of $ 25.308,17, with respect to the statement of income, total income of $ 1.194,73 and total expenses of $ 706,43; generating a profit for the year of $ 415,06; likewise, the cash flow statement reflects a balance for operating activities of $ -2.474,14; financing activities of $ -446,40; to which is added the initial balance of $ 13,878.36 obtaining a final balance of $ 10.957,82; of which $ 797,64 corresponds to the cash account and $ 10. 160.18 to the bank account; finally, the statement of cost of products sold was prepared, which shows a real cost of product sold of $ 5.254,27; by adding the direct raw material with a value of $ 2.089,93; direct labor $ 1.500,96; indirect manufacturing costs $ 116,22 and variation of the cost with a value of $ 1.547,16.